2018
DOI: 10.1016/j.addbeh.2017.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Young adult e-cigarette use outcome expectancies: Validity of a revised scale and a short scale

Abstract: The revised youth e-cigarette outcome expectancies measure adds new items informed by recent qualitative research with young adult e-cigarette users, especially in the domain of positive "smoking" experience. Positive "smoking" experience represents beliefs that use of e-cigarettes provides outcomes associated with a better "smoking" alternative: for example, an alternative that is more socially approved, more suitable for indoor use, and that provides a safer means of enjoying nicotine. In addition, we tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 29 publications
5
40
0
Order By: Relevance
“…Three variables were found to be associated with use intentions via curiosity: positive expectancies about e‐cigarettes, having a larger number of family members who use e‐cigarettes, and having a larger number of friends who smoke conventional tobacco cigarettes. Of these, positive expectancies were found to be the most important, consistent with previous research on the factors associated with e‐cigarette use . Given previous research on the effects of e‐cigarette advertising among young adult non‐smokers has shown that positive portrayals of e‐cigarettes result in more favourable attitudes to the devices , maintaining existing regulations on the marketing of e‐cigarettes in Australia and other countries with similarly restrictive regulatory environments (e.g.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Three variables were found to be associated with use intentions via curiosity: positive expectancies about e‐cigarettes, having a larger number of family members who use e‐cigarettes, and having a larger number of friends who smoke conventional tobacco cigarettes. Of these, positive expectancies were found to be the most important, consistent with previous research on the factors associated with e‐cigarette use . Given previous research on the effects of e‐cigarette advertising among young adult non‐smokers has shown that positive portrayals of e‐cigarettes result in more favourable attitudes to the devices , maintaining existing regulations on the marketing of e‐cigarettes in Australia and other countries with similarly restrictive regulatory environments (e.g.…”
Section: Discussionsupporting
confidence: 85%
“…This research indicates that individuals who believe e‐cigarettes are less harmful than conventional cigarettes are more likely than those who do not hold this belief to use the devices . Some evidence is beginning to emerge on e‐cigarette expectancies, with research suggesting that beliefs about the positive experiences associated with e‐cigarette use (e.g., feeling relaxed) are linked with use of the devices . Although previous research suggests that sensation seeking traits are a major correlate of drug use and conventional cigarette smoking , just one study to date appears to have been conducted assessing the association between this individual personality trait and e‐cigarette use in young adults .…”
Section: Introductionmentioning
confidence: 94%
“…Although the popularity of electronic smoking differs among European countries [7], it is common to hear about the growing popularity of vaping as such and of the emergence of a new concern for public healthcare and health (the effect on the organism of substances constituting e-liquid, including nicotine; the use of an e-cigarette as a source of cannabinoids and other prohibited drugs) [8][9][10]. Due to the short time of availability of electronic cigarettes, knowledge about their possible impact on human health is obscure [1].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, studies have begun to extend this work to e-cigarettes. In a recent survey developed in part from qualitative interviews with young adult e-cigarette users, Pokhrel and colleagues (Pokhrel, Lam, Pagano, Kawamoto, & Herzog, 2018) demonstrated associations between young adults' positive and negative outcome expectations and e-cigarette willingness, use, and dependence. Positive youth outcome expectancies have also recently been linked with ecigarette initiation in a longitudinal study (Creamer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%